2008
DOI: 10.1016/j.compscitech.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

3D simulation of macroscopic heat and mass transfer properties from the microstructure of wood fibre networks

Abstract: To cite this version:Heiko Thoemen, Thomas Walther, Andreas Wiegmann. 3D simulation of macroscopic heat and mass transfer properties from the microstructure of wood fibre networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…We then use our circumscribed equivalent media to predict these results. GeoDict is a voxel-based code developed by Fraunhofer ITWM, and validated in many recent publications by our group and others [26][27][28][29][30]. Our previous voxel size independence has revealed that consistent results can be obtained from GeoDict by using 15 or more voxels per fiber diameter.…”
Section: Test Case: Performance Of 3-d Filter Media With Ar = 15 Svmentioning
confidence: 70%
“…We then use our circumscribed equivalent media to predict these results. GeoDict is a voxel-based code developed by Fraunhofer ITWM, and validated in many recent publications by our group and others [26][27][28][29][30]. Our previous voxel size independence has revealed that consistent results can be obtained from GeoDict by using 15 or more voxels per fiber diameter.…”
Section: Test Case: Performance Of 3-d Filter Media With Ar = 15 Svmentioning
confidence: 70%
“…Findings by Rolland du Roscoat et al (2007) and Lux et al (2006) for the representative elementary volume of tomography data of paper were taken into consideration. Furthermore, the results of the permeability and thermal conductivity experiments and simulation presented by Thoemen et al (2008) showed that the chosen sub-volume size was representative.…”
Section: Mdf Tomography Datamentioning
confidence: 98%
“…Nevertheless, the polynomial relationship between density and transverse conductivity given by Thoemen et al [10] is not applicable due to the low density of our medium. The total thermal conductivity is known with accuracy by measurements made on a guarded hot plate device: k t ¼ 4.2 AE 0.1 Â 10 À2 W m À1 K À1 at 20 C for a dry sample.…”
Section: Description Of the Materials And Experimental Methodsmentioning
confidence: 98%
“…The exact phonic conductivity of the medium is unknown as even the recent study of Lux et al [2] gave this physical quantity with an error of 30%. Besides, Thoemen et al [10] recently presented a method to determine both macroscopic permeability and thermal conductivity from the microstructure of wood fibre networks with densities ranging from 500 to 1360 kg m À3 . The thermal conductivity measured with a fluxmeter device showed agreement of the computed value within experimental error, with respect to the model assumptions.…”
Section: Description Of the Materials And Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation